Mechanisms for Modulating Anoikis Resistance in Cancer and the Relevance of Metabolic Reprogramming - Adeshakin, Funmilayo O.; Adeshakin, Adeleye O.; Afolabi, Lukman O.; Yan, Dehong; Zhang, Guizhong; Wan, Xiaochun (Frontiers in Oncology, 2021)
The attachment of cells to the extracellular matrix (ECM) is the hallmark of structure–function stability and well-being. ECM detachment in localized tumors precedes abnormal dissemination of tumor cells culminating in metastasis. Programmed cell death (PCD) is activated during tumorigenesis to clear off ECM-detached cells through “anoikis.” However, cancer cells develop several mechanisms for abrogating anoikis, thus promoting their invasiveness and metastasis. Specific factors, such as growth proteins, pH, transcriptional signaling pathways, and oxidative stress, have been reported as drivers of anoikis resistance, thus enhancing cancer proliferation and metastasis. Recent studies highlighted the key contributions of metabolic pathways, enabling the cells to bypass anoikis. Therefore, understanding the mechanisms driving anoikis resistance could help to counteract tumor progression and prevent metastasis. This review elucidates the dynamics employed by cancer cells to impede anoikis, thus promoting proliferation, invasion, and metastasis. In addition, the authors have discussed other metabolic intermediates (especially amino acids and nucleotides) that are less explored, which could be crucial for anoikis resistance and metastasis.